2017
DOI: 10.1016/j.psychres.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Invariance of the Internet Gaming Disorder Scale–Short-Form (IGDS9-SF) between the United States of America, India and the United Kingdom

Abstract: The Internet Gaming Disorder Scale-Short-Form (IGDS9-SF) has been extensively used worldwide to assess Internet Gaming Disorder (IGD) behaviors. Therefore, investigating cultural limitations and implications in its applicability is necessary. The cross-cultural feasibility of a test can be psychometrically evaluated with measurement invariance analyses. Thus, the present study used Multigroup Confirmatory Factor Analysis (MGCFA) to examine the IGDS9-SF measurement invariance across gamers from the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
82
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 47 publications
(75 reference statements)
15
82
3
1
Order By: Relevance
“…The results of the EFA and CFA yielded statistically significant and relatively high factor loadings, further demonstrating that all items were adequate indicators of the IGD construct and that the scale had adequate psychometric properties, alongside a solid factor structure. In the original study, the IGDS9-SF showed adequate reliability (α = 0.87), whereas Cronbach's alphas ranged between 0.87 and 0.96 in subsequent studies (Monacis et al, 2016;Pontes et al, 2017;Wu et al, 2017). Consistent with these reliability findings previously reported, the Turkish version obtained similar for the newly developed IGDS9-SF (α = 0.89).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results of the EFA and CFA yielded statistically significant and relatively high factor loadings, further demonstrating that all items were adequate indicators of the IGD construct and that the scale had adequate psychometric properties, alongside a solid factor structure. In the original study, the IGDS9-SF showed adequate reliability (α = 0.87), whereas Cronbach's alphas ranged between 0.87 and 0.96 in subsequent studies (Monacis et al, 2016;Pontes et al, 2017;Wu et al, 2017). Consistent with these reliability findings previously reported, the Turkish version obtained similar for the newly developed IGDS9-SF (α = 0.89).…”
Section: Discussionsupporting
confidence: 77%
“…Although these international studies utilizing the IGDS9-SF have not directly estimated mean scores of IGD across different populations investigated due to their exclusive psychometric focus, these studies have provided key insights on the diagnosis and measurement of IGD. For example, these studies have collectively established that IGD is better conceptualized as a one-factor construct as opposed to a multidimensional construct, and that significant cultural differences may exist regarding the clinical importance of each of the nine IGD criteria across different populations (e.g., de Palo et al, 2018;Pontes et al, 2017;Stavropoulos et al, 2018). Furthermore, a recent study investigating the invariance of the IGD construct in a sample of Australian, North American, and British gamers found significant cross-country variations in the strength of the relationships between the IGD indicators and their respective factor as the IGDS9-SF items 1, 2 and 5 presented non-invariant loadings across the three populations investigated .…”
Section: Introductionmentioning
confidence: 99%
“…The nine IGD criteria comprise (i) preoccupation with OG; (ii) withdrawal symptoms when OG is prevented; (iii) tolerance, with a progressive increase of OG over time; (iv) using OG to escape or relieve negative mood (e.g., anxiety); (v) unsuccessful attempts to control OG; (vi) continuing excessive OG despite awareness of the risks; (vii) loss of interest in alternative forms of entertainment/satisfaction; (viii) deceiving important/close others regarding time spent OG; and (ix) jeopardizing or losing a significant relationship, job, or educational/career opportunity because of OG. Since the introduction of IGD, researchers and clinicians have begun to converge internationally on its use (when referring to excessive OG), as described in the DSM-5, and have (in the main) applied psychometric measures with high IGD construct validity (Gomez et al 2018a;Pontes et al 2017a;Stavropoulos et al 2018c).…”
Section: Disordered Gamingmentioning
confidence: 99%
“…The latter socio-demographic figures contradict the widespread stereotype of gamers being adolescent males (Griffiths et al 2003). Overall, the rapid growth of OG has been interwoven with uncertainties about which populations are primarily engaged, and OG's effect on well being (Anderson et al 2017;Kuss and Griffiths 2012;Pontes et al 2017a;Stavropoulos et al 2018b). Despite OG having many positive psychosocial effects 1 beyond satisfying one's leisure needs Carras et al 2018;Jones et al 2014), for excessive gamers, psychosocial repercussions can be multiple, 2 compromising their concurrent and future adaptation (Anderson et al 2017;Beard et al 2017;Kuss and Griffiths 2012;Kuss et al 2017;Pontes et al 2017b;Kuss et al 2018;Stavropoulos et al 2018aStavropoulos et al , 2018bStavropoulos et al 2019).…”
mentioning
confidence: 99%
“…There are also studies showing that some gamers immerse within the game that can result in problematic usage (e.g., Lemmens et al 2011;Peters and Malesky 2008;Pontes et al 2017;Rehbein et al 2010;van Rooij et al 2010). The deep immersion in playing videogame can be both a conscious and unconscious action, and for a minority of players, they can perceive themselves as being addicted to gaming (Kuss and Griffiths 2012).…”
mentioning
confidence: 99%